English Speaking Instructional Model at Senior High School: A Single Case Study at SMAN 01 Sutojayan, Blitar, East Java - Ahmad Nur Khusaini; Supriyono Supriyono; Adin Fauzi; Hesty Puspita Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines English language education at SMAN 1 Sutojayan Blitar using a qualitative case study. Data were collected through interviews, observations, and document analysis, focusing on planning, organization, implementation, and assessment. The findings reveal that English teaching at the school is highly structured and effective. Key elements include detailed planning, diverse instructional methods, and a student-centered approach. The curriculum is regularly updated to align with students' skill levels, and clear role delegation, strong coordination, and efficient resource use contribute to a positive learning environment. The communicative approach, technology integration, and varied teaching techniques promote active student participation. A comprehensive assessment system provides continuous feedback, supporting learning progress. Overall, the study highlights the importance of holistic teaching strategies that enhance students' English-speaking skills and can serve as a model for improving English language education.